Essays in economic theory, growth, and labour markets : a festschrift in honour of E. Drandakis - Bitros, George; Drandakis, Emmanuel; Katsoulacos, Y. S., 1953- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
This book analyzes the numerous incentives which arises from social security benefits, labour market institutions, and the way in which the firms are organised with respect to these relationships. It highlights the need for dynamic general equilibrium multi-sectoral models which help us better understand the future developments of industrialised economics..
Includes bibliographical references and index.
nmn 22/10/13
Loans
Keywords: Labor market; Economics